Matchmaking in Pesantren: The Role of Wali Mujbir in Matchmaking with Maqasid Sharia Perspectives - Sallom, Dea Salma; Syu'aib, Kholil (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
Wali mujbir is a guardian who has the right to marry off his daughter with or without the permission of the person concerned with certain conditions. He is someone who has an upward patrilineal line with the woman who will marry, which in this case is the father. In Islam, the right of wali mujbir is usually called the right of ijbar, this right is absolute, but as time goes by, now the privilege of ijbar has another interpretation. Although the father has the right to force him, he does not forget to allow his daughter to have an opinion. This kind of marriage is often referred to as matchmaking. It is considered an interesting social phenomenon in society. Pesantren, as sacred institutions, are often the mecca in matchmaking processions because, in pesantren, families prioritize lineage in finding a partner. It is an important benchmark for dzurriyah or the descendants of the Kiai. In addition to maintaining lineage, matchmaking in pesantren also aims to preserve religion and soul. This article examines the role of wali mujbir at the APTQ Bungah Gresik pesantren in carrying out matchmaking so that the goals of sharia are achieved, which in this case are hifdz ad-din, hifdz an-nafs, and hifdz an-nasl.